2018
DOI: 10.2106/jbjs.rvw.17.00201
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Arthroscopic Simulation in Teaching Surgical Skills

Abstract: Background: Following the introduction of worktime regulations across the world along with existing concerns over the nonuniform nature of the traditional apprenticeship model, an alternative method for teaching surgical skills is being sought. Simulation training offers a safe and standardized environment to develop and improve surgical skills. The purpose of the present study was to review the existing and most recent research into the utility of arthroscopic simulators in training and the teachi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 73 publications
0
9
0
7
Order By: Relevance
“…Inhaltsvalidität ("content validity") bezeichnet die Messung verschiedener arthroskopischer Fähigkeiten [26,27,29]. Am besten eignen sich dazu objektive Messparameter (z.…”
Section: » Inhaltsvalidität Bezeichnet Die Messung Verschiedener Arthunclassified
See 1 more Smart Citation
“…Inhaltsvalidität ("content validity") bezeichnet die Messung verschiedener arthroskopischer Fähigkeiten [26,27,29]. Am besten eignen sich dazu objektive Messparameter (z.…”
Section: » Inhaltsvalidität Bezeichnet Die Messung Verschiedener Arthunclassified
“…So konnten verschiedene Studien zeigen, dass sich die für die jeweilig abgefragte arthroskopische Aufgabe benötigte Zeit insbesondere bei Anfängern mit der Anzahl der Wiederholungen verkürzt [27]. Bei Fortgeschrittenen war dieser Effekt nicht in allen Studien signifikant [26,29].…”
Section: » Inhaltsvalidität Bezeichnet Die Messung Verschiedener Arthunclassified
“…Simulators of varying fidelities will be needed to optimize training curricula. 23 Medium-and highfidelity (VR) simulations will be particularly valuable for training more complex tasks, as well as exhibiting varied and even patient-specific pathologies. As the sophistication of VR simulators continue to evolve, they will be required not only to determine whether tasks were completed but also to assess whether errors were enacted.…”
Section: Simulator-based Skills Trainingmentioning
confidence: 99%
“…In particular, there is heightened interest in implementing arthroscopic simulation into orthopaedic residency training. 3,4 Currently, a plethora of arthroscopic trainers, which range from low-fidelity, nonanatomic simulation models, such as triangulation box systems, to high-fidelity simulation models, such as anatomic virtual-reality systems, are available. Simulation offers trainees a protected, controlled environment in which they can practice and acquire skills safely outside of the operating room.…”
mentioning
confidence: 99%
“…Despite the proposed advantages of simulation training, there remains no consensus gold-standard simulation model or protocol. 4 Authors have shown that some anatomic knee and shoulder simulators can be valuable arthroscopy training tools and may aid in the development of skills transferable to cadaveric or patient models. 10e13 However, several anatomic virtual-reality or laboratory-based trainers may be impractical or cost prohibitive, leading to barriers to implementation.…”
mentioning
confidence: 99%